2013
DOI: 10.1007/s13337-012-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

H1N1 influenza A virus Related Pneumonia and Respiratory Failure

Abstract: Influenza viruses are common respiratory pathogens in humans and can cause serious infection that leads to the development of pneumonia. In this study, the clinical and laboratory features of 36 patients from Turkey who are hospitalized in intensive care unit due to pandemic influenza A (H1N1) associated pneumonia and respiratory failure were retrospectively evaluated. The most common symptoms were cough and fever. Consolidation (36.1 %) and interstitial changes (30.6 %) were the most frequently identified fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Several studies have shown that severe and critically ill individuals during viral infection (such as SARS-CoV-2 or EBOV or AIV), who required intensive care unit (ICU), had obviously lower lymphocyte counts compared to those in healthy, mild or recovered individuals [ 13 , 172 , 173 , 174 ]. This phenomenon indicated that the degree of lymphocyte count has been associated with disease severity [ 174 , 175 , 176 ]. T cells play a critical role in virus-specific, adaptive immune response, thereby suggesting that lymphopenia could severely impair the body’s ability to fight infection.…”
Section: Clinical Implications Of Lymphopenia During Viral Infectionsmentioning
confidence: 99%
“…Several studies have shown that severe and critically ill individuals during viral infection (such as SARS-CoV-2 or EBOV or AIV), who required intensive care unit (ICU), had obviously lower lymphocyte counts compared to those in healthy, mild or recovered individuals [ 13 , 172 , 173 , 174 ]. This phenomenon indicated that the degree of lymphocyte count has been associated with disease severity [ 174 , 175 , 176 ]. T cells play a critical role in virus-specific, adaptive immune response, thereby suggesting that lymphopenia could severely impair the body’s ability to fight infection.…”
Section: Clinical Implications Of Lymphopenia During Viral Infectionsmentioning
confidence: 99%
“… 14 Moreover, Castelli et al 15 found that in elderly individuals with pulmonary embolism, serum LDH level was a good predictor of short-term mortality due to the applicability and simpleness for routine use based on common clinical practice. In a recently published study conducted by Okur et al , 16 concerning the clinical and laboratory features of those with respiratory failure and pneumonia caused by H1N1 influenza A virus, mortality was demonstrated to be significantly associated with an elevated serum LDH level. Similar inter-relations were observed from overall survival in patients with metastatic renal cell carcinoma, 17 diagnosis of acute respiratory distress syndrome in the population at risk, 18 early mortality in peritonitis-induced sepsis 19 and mortality in postinfarction myocardial rupture.…”
Section: Discussionmentioning
confidence: 96%
“…Konsolidasyon ve interstisiyel değişiklikleri en sık gözlenen radyolojik anormallikler olarak belirtmişlerdir. 8 Mortalite, altta yatan hastalığı olanlarda %23,1 olarak gö-rülmüştür. Bizim olgumuzda da radyolojik olarak konsolidasyon gözlendi.…”
Section: Hızlı Progresyon Ve Akut Solunum Sıkıntısı Sendromu Ileunclassified